(untitled) (Publicaciones en Ciencias y Tecnología, 2012)
In this article is considered developting through a theoretical framework, the formulation of university research as a guiding priciple of the University, allowing it to be transformed in an intelligent Organization, and yielding the linking of the university areas of knowledge to society. This raises the importance of managing knowledge as an indispensable element in the transformations that require higher education institutions, turning university research into the social hub of knowledge transfer. This involves a review of the theoretical constructs related to the University Management, Social Constructionism, Intelligent Organization and Lines of Action Research, ending with a proposal of linking university research and the productive sector which includes, rst, the creation of university spin-o s as a suitable alternative to bridge the information gap and knowledge transfer between universities and traditional companies. Secondly, the development of innovative research management is proposed, which allows systematic channeling of the e orts of researchers, raising funds and the transfer of research results.